Electrical stratigraphy of the WAIS Divide ice core: Identification of centimeter‐scale irregular layering. Issue 7 (12th July 2016) - Fudge, T. J.; Taylor, Kendrick C.; Waddington, Edwin D.; Fitzpatrick, Joan J.; Conway, Howard
Abstract: Multitrack electrical conductivity measurements imaged a continuous record of the two‐dimensional electrical stratigraphy for the deepest 40% of the WAIS Divide ice core (1956 m to 3405 m, 11.5 to 68 ka). The electrical stratigraphy showed clear banding driven primarily by annual variations. Centimeter‐scale pinched layers and other irregularities were concentrated between 2700 m and 2900 m (27 ka to 33 ka); below 2900 m, decreasing amplitude of conductance variations likely due to diffusion prevented confident interpretation of both annual and irregular layering. The effective diffusivity at −30°C is 2.2 × 10 −8 m 2 yr −1, approximately 5 times greater than for self‐diffusion of water molecules, implying diffusion at grain boundaries. The irregular layering indicates that the centimeter‐scale layering was disturbed in sections even though other records, such as atmospheric methane, indicate meter and larger layering is not compromised. Preservation of irregular layering at deposition is unlikely to be the cause of the identified irregular layering; instead, the irregular layering likely arises from variations in the deformation of ice. Key Points: Centimeter‐scale irregular layering was observed with boudinage due to viscosity contrasts of fine‐ and coarse‐grain layers a possible mechanism Diffusion obscures the layering in the deepest ice and ended the annual layer interpretation The amount of diffusion and irregular layering will be important considerations for future ice cores seeking to recover ice near the bed